1997
DOI: 10.1021/np970246q
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Donaxaridine

Abstract: The first total synthesis of donaxaridine (1) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(46 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…The simple amino acids bearing only an amino group and a carboxyl group could not catalyze this reaction. No expected aldol adducts were observed after direct determination by TLC (Table 1, entries [1][2][3][4][5]. This indicated that it is impossible for the aldol reaction in which these primary amine and secondary amine catalysts unilaterally activate the (E)-4-phenylbut-3-en-2-one (2a) to form an enamine intermediate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simple amino acids bearing only an amino group and a carboxyl group could not catalyze this reaction. No expected aldol adducts were observed after direct determination by TLC (Table 1, entries [1][2][3][4][5]. This indicated that it is impossible for the aldol reaction in which these primary amine and secondary amine catalysts unilaterally activate the (E)-4-phenylbut-3-en-2-one (2a) to form an enamine intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic properties and steric hindrance of the substituents at the aromatic ring influenced the yields slightly. Generally, α,β-unsaturated ketones with electron-donating groups gave higher yields than those with electron-withdrawing groups (Table 2, entries 2, 10 vs. [3][4][5][6][7][8]. Ortho-and meta-substituted α,β-unsaturated ketones gave higher yields than para-substituted α,β-unsaturated ketones ( Table 2, entries 2-5 vs. [8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral High-performance liquid chromatography (HPLC) analysis was conducted with a Waters Alliance 2695 instrument (Waters corporation, Milford, MA, USA), using a UV-visible light (Vis) Waters PDA 2998 detector (Waters corporation), and working at 254 nm. 1 H NMR spectra were recorded on a Bruker AM400 NMR spectrometer (Bruker corporation, Karlsruhe, Germany), and NMR spectra were obtained as CDCl3 solutions (reported in ppm), using chloroform as the reference standard (7.26 ppm) or dimethyl sulfoxide-d6 (DMSO-d6)(2.50 ppm). High-resolution mass …”
Section: General Methodsmentioning
confidence: 99%
“…The 3-substituted-3-hydroxy-2-oxindoles have a stereogenic quaternary center at the C-3 position and a core unit that appears in many natural products and biologically active compounds [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%